Acute COVID-19 cardiovascular syndrome: A case report - Agus Layanto; Sofyan Rais Addin; Friska Anggraini Helena Silitonga; Ayudyah Nurani; Rakhma Yanti Hellmi; Charles Limantoro; K Heri Nugroho Hario Seno; Fathur Nur Kholis (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
A man 44 years old with metabolic syndrome and chronic kidney disease was presenting acute COVID-19 cardiovascular syndrome. The condition was aggravated by presence of ureterolithiasis and gout. After treatment, hemodialysis and ureteroscopic lithotripsy-double J ureteral stent, the patient was recovered from his condition